Pengaruh Lokasi Kenyamanan Tempat, Dan Kualitas Produk Terhadap Keputusan Pembelian Di Warkop Puntadewa Pakis Kabupaten Malang (Studi Kasus Konsumen Warkop Puntadewa Pakis Kabupaten Malang) - Moh. Afifuddin; Budi Wahono; Sulton Sholehuddin (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine the effect of location, convenience of place, and product quality on purchasing decisions at warkop Puntadewa Pakis Malang district. The data method in this study used a questionnaire with a total sample of 65 respondents. The analytical method used in this study is multiple linear analysis by testing the hypothesis using the F test and t test. Based on the results of data analysis, it is explained that the independent variables consist of location, convenience of place, product quality, while the dependent variable is the purchase decision. From the results of the research above it can be seen that location, convenience of place, and product quality simultaneously influence purchasing decisions. Keywords: Location, Place Convenience, Product Quality, and Purchase Decision